The Effect of Training Program Using Electronic Style and In Field During Covid-19 on The Development of Some Physical Traits in Karate Athlete - Noori, Saman Faiq; Abdullah, Shilan Sdiq (Journal of Physical Education, 2021)
The research aimed at designing a training program using electronic and in-field training to identify the differences between tests for both groups. In addition to that, it aimed at identifying the differences between posttests for both groups under study. Karate athletes from Karate Improvement Organization in Sulyamania governorate. The researchers used the experimental method on (12) athletes to conclude that electronic learning group has developed in some physical abilities understudy compared to pretest in favor of the posttests. The electronic style used by the experimental group highly affected the psychological, functional, and emotional aspects of athletes during COVID 19. In addition to that, the results showed that using both electronic and in-field training has a positive effect on developing special physical abilities.